Great Christian jurists in the Low Countries - Decock, Wim; Oosterhuis, Janwillem (Law and Christianity, 2021)
"The present volume wants to reveal the impact of Christianity on the development of law and societal policies in the Low Countries over a period of ten centuries. It starts with the seminal contribution to the medieval ius commune by the canonist Alger de Liège (ca. 1060-1132) at the end of the eleventh century and ends with Josse Mertens de Wilmars's (1912-2002) protagonist role as a judge in the creation of a European ius commune in the second half of the twentieth century. The impact of Christianity on thinking and making the law is shown through essays on twenty Christian legal scholars and legal practitioners from the Low Countries. Historically speaking, the Low Countries cover a region which, today, is more or less corresponding to Belgium, the Netherlands, Luxembourg and parts of Northern France. Through these biographies from jurists from the Southern and Northern Netherlands, developments that are more general in nature can be recognised and established, about the changing roles of Christianity and law in Western societies more general. As a matter of fact, the gradual "secularization" of legal culture in the Low Countries is used as a framework to describe the general evolution of the impact of Christianity on the lives and writings of the twenty selected jurists"--